An Analysis of the Ability to Understand Mathematical Concepts of Middle School Students in Completing Integer Operations - Teguh Wibowo; Prasetyo Budi Darmono; Haliza Nur Azieta (Universitas Sriwijaya, 2022)
Understanding mathematical concepts is a crucial skill for students to possess because it will make it easier for students to learn and master concepts in mathematics. This study aimed to describe the ability to understand mathematical concepts of junior high school students in solving integer arithmetic operations. This type of research was descriptive qualitative. The subjects in this study were seventh-grade students in one of the public junior high schools in Purworejo district in the 2020/2021 academic year with a good understanding. The technique of selecting the subject was purposive and snowball. The data analysis technique employed was the analysis technique of Miles & Huberman; data reduction, data presentation, and conclusion drawing. The results of this study indicated that students' understanding of mathematical concepts in completing arithmetic operations were as follows; students could restate a concept in writing, students could provide examples and not examples of a concept they have learned, students could use and choose certain operations in solving mathematical problems, students could not present concepts in the form of mathematical representations in the form of pictures, students could not classify objects according to certain properties according to the concept, and students could not apply the concept algorithmically to problem-solving.